2009
DOI: 10.1097/nrl.0b013e3181a93bac
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Deep Venous Thrombosis and Pulmonary Embolism in Patients With Acute Intracerebral Hemorrhage

Abstract: Low dose heparin treatment after 48 hours of stroke in ICH patients is not associated with an increased hematoma growth and should be used for DVT and PE prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
64
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 11 publications
0
64
0
3
Order By: Relevance
“…[16][17][18][19][20][21] Three small randomized trials have also been completed. [22][23][24] In 68 patients with ICH, low-dose heparin starting on day 2 led to a statistically lower rate of PE when compared with 4th or 10th day of initiation. 24 The second trial included 46 patients and found that low-dose subcutaneous heparin did not increase risk of rebleeding or hematoma expansion.…”
Section: February 2015mentioning
confidence: 97%
See 1 more Smart Citation
“…[16][17][18][19][20][21] Three small randomized trials have also been completed. [22][23][24] In 68 patients with ICH, low-dose heparin starting on day 2 led to a statistically lower rate of PE when compared with 4th or 10th day of initiation. 24 The second trial included 46 patients and found that low-dose subcutaneous heparin did not increase risk of rebleeding or hematoma expansion.…”
Section: February 2015mentioning
confidence: 97%
“…23 A more recent trial of 75 patients using enoxaparin also observed no increase risk of hematoma expansion. 22 A meta-analysis of 4 controlled (2 randomized) 17,21,22,24 studies suggested a significant reduction in PE with prophylactic anticoagulation with no effect on DVT occurrence or bleeding. 25 Despite previous studies showing modest benefits in reducing PE balanced partly by risk of bleeding in medically ill and hospitalized patients with stroke, [26][27][28] current American Heart Association/American Stroke Association guidelines recommend prophylactic anticoagulation (class I, level of evidence A) in immobilized patients with acute ischemic stroke.…”
Section: February 2015mentioning
confidence: 99%
“…23 In contrast with the FAST study, the majority of our patients with thromboembolic events had venous thromboembolic complications, which are known to be prevalent in hospitalized patients with ICH, especially with limb immobility. 24 Of the 10 patients with DVTs, 3 were possibly associated with Peripherally Inserted Central Catheter lines and may not have been directly related to rFVIIa because they all occurred Ͼ1 week after rFVIIa administration. Although 3 patients in our study had strokes, 2 of them took place several weeks after rFVIIa infusion in patients with atrial fibrillation who had remained off warfarin since the bleeding.…”
Section: Robinson Et Al Safety Of Factor VII In Warfarin-associated Ichmentioning
confidence: 99%
“…The risk of venous thromboembolism is high in an immobilized patient after any type of stroke and low-molecular-weight heparin at a prophylactic dose, started after 48 hours in patients with intracerebral hemorrhage appears to be safe. 8 In summary, for this patient, warfarin should most likely not be restarted. However, if he belongs to the minority with deep hemispheric hemorrhage, resumption could be considered, although it is worrisome if no triggering factor for the index bleeding was identified.…”
mentioning
confidence: 97%
“…Риск развития веноз-ной тромбоэмболии наиболее высок у обездвиженных пациентов после любого типа инсульта, поэтому введе-ние низкомолекулярного гепарина в профилактичес-кой дозе через 48 часов пациентам с внутримозговым кровоизлиянием, по всей видимости, безопасно [8].…”
unclassified